Insegnare (e imparare) la chimica attraverso i musei e le collezioni di strumenti scientifici - Domenici, Valentina; Angelici, Gaetano (Chimica nella Scuola, 2025)
In this paper, the educational potential of historical scientific instruments was explored and implemented as part of a special teaching project supported by the University of Pisa during the 2023-2024 academic year. The project, titled Teaching (and Learning) Chemistry through Museums and Collections of Scientific Instruments, was coordinated by the authors of this article and it served as an integrative activity for the optional courses “Fundamentals and Methodologies for Teaching Chemistry Education” (Bachelor’s Degree in Chemistry) and “Introduction to Medicinal Chemistry” (Master’s Degree in Chemistry). The project involved fifteen students and resulted in the valorisation and enhancement of part of the collection of historical scientific instruments of the Department of Chemistry and Industrial Chemistry at the University of Pisa. Moreover, the undergraduate students actively contributed in creating the museum collection’s website, enriched with historical and educational descriptions of the instruments. This collaborative work later enabled the undergraduate students to conduct demonstration teaching activities for high school students, which were presented during a concluding event of the project. This article will detail the various steps of the activity and discuss its educational, formative, and cultural outcomes, also taking into account the feedback received from the students.